Inibição da atividade contrátil de preparações isoladas de esôfago de rato por ácidos biliares: papel do receptor Tgr5 - Gadelha, Kalinne Kelly Lima (2024)
In gastroesophageal reflux disease frequent contact occurs between the esophageal mucosa and gastric acid and other constituents, such as bile acids and pepsin. In a previous study, bile acids reduced the contractility of the esophagus. In this study, we delve into the evaluation of the mechanism of action of bile acids in inhibiting esophageal contractility. To do this, we recorded isometric contractions of segments of the esophagus from Wistar rats subjected to refluxate enriched with bile acids using a data acquisition system. Furthermore, esophageal contractions were tested in the presence of isolated bile acids, as well as in the presence of TGR5 agonists, the membrane receptor for bile acids. To study the signaling pathway, levels of cAMP were measured by ELISA, and the expression of the TGR5 receptor was evaluated through confocal microscope fluorescence images and western blot. When challenged with refluxate, the esophageal segments were mounted in glass chambers to capture responses from the circular and longitudinal muscle layers. After being exposed for 30 minutes to Tyrode solution at pH 1 or Tyrode solution at pH 1 enriched with pepsin, esophageal segments did not show differences in contractile responses caused by KCl or CCh compared to those exposed to the control solution (Tyrode pH 7.4). However, when the bile acids TDCA and DCA were added to the refluxate, the contractile response of the esophageal segments to KCl was significantly reduced. A significant reduction was also observed in cholinergic contractions after pre-exposure to DCA, TDCA, and oleanolic acid (TGR5 agonist). The reduction in esophageal contractility in response to bile acids was attenuated by triamterene (a TGR5 antagonist) and MDL-12330A (an adenylate cyclase inhibitor). Levels of cAMP were increased in segments exposed to DCA for 30 minutes, as well as the expression of TGR5 and PKA. The results suggest that esophageal dysmotility may be related to the action of bile acids on TGR5 receptors, allowing for further investigations into the signaling pathways involved.